Reconciling Muslim Tradition and Modern Science: An Exploratory Study of Nidhal Guessoum’s Thought - Nur Rofiq; M. Zidny Nafi’ Hasbi (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2021)
This paper aims to find out the results of Nidhal Guessoum's thoughts on his studies on Islam and contemporary science issues contained in his book entitled "Islam's Quantum Question: Reconciling Muslim Tradition and Modern Science". Nidhal Guessoum's thoughts in the book, particularly in the Islamic section and contemporary science issues that can be understood through the four subsections he divides namely (1) Islam and Cosmology, which discuss Islam about the way one expresses his views freely; (2) Islam and the Rancanan Argument, which is about Islam and the arguments expressed by men such as about the law or social experience; (3) Islam and the Anthropic Principle, which deals with Islam and the revolution of human scientific thought, and (4) Islam and Evolution, which is to discuss Islam and the process of human evolution based on Darwin's theory. Abstrak: Tulisan ini bertujuan untuk mengetahui hasil pemikiran Nidhal Guessoum tentang kajian Islam dan isu-isu sains kontemporer yang tertuang dalam bukunya yang berjudul “Islam’s Quantum Question: Reconciling Muslim Tradition and Modern Science”. Pemikiran Nidhal Guessoum dalam buku tersebut, khususnya pada bagian Islam dan isu-isu sains kontemporer yang dapat dipahami melalui empat sub-bab yaitu, (1) Islam dan Kosmologi, yakni yang membahas mengenai Islam kaitannya dengan cara seseorang mengutarakan pandangan-pandangannya secara bebas; (2) Islam dan Argumen Rancanan, yakni yang membahas mengenai Islam dan argumen-argumen yang diutarakan manusia seperti tentang hukum atau pengalaman sosial; (3) Islam dan Prinsip Antropik, yakni yang membahas tentang Islam dan revolusi pemikiran ilmiah manusia, serta (4)Islam dan Evolusi, yakni membahas tentang Islam dan proses evolusi manusia berdasarkan teori Darwin.